Chimeric crRNAs Retaining Activity of Cas12a with Potential to Improve Specificity. (30th September 2020) - Park, Jihyun; Choi, Jaewoo; Duong, Men Thi Hoai; Ahn, Hee‐Chul; Hong, Seung Woo; Hwang, Gil Tae; An, Jinsu; Chung, Hak Suk; Ahn, Dae‐Ro
Abstract : RNA residues in the guide region of crRNA for Cas12a can be partially replaced by DNA.